Beeld in Park in Beeld. - Félix Hap Park, Brussel (Etterbeek : Felix Happark, 1990)
Camps, Leo ; Claes, Frans ; Crombe, Patrick ; Decaestecker, Lea ; Dederen, Gérald ; Eijberg, André ; Frantzen, Tom ; Haar, Marie-Paul ; Ketele, Alexander ; Majerus, Pierre ; Peters, Teo ; Rohr, Renée ; Strebelle, Olivier ; Tignee, Paul ; Tinel, Koen ; Van Sumere, Hilde ; Verhellen, Tjerrie ; Wille, Jonas
Beeld in Park in Beeld, Felix Happark, Brussel, van 7 september tot 12 oktober 1990
boek